Two-dimensional electronic spectroscopy signatures of the glass transition. Issue 3 (2010) - Lewis Lewis, K. L .M. K. L .M.; Myers Myers, J. A. J. A.; Fuller Fuller, F. F.; Tekavec Tekavec, P. F. P. F.; Ogilvie Ogilvie, J. P. J. P.
Abstract : Two-dimensional electronic spectroscopy is a sensitive probe of solvation dynamics. Using a pump–probe geometry with a pulse shaper [ Optics Express 15 (2007), 16681-16689; Optics Express 16 (2008), 17420-17428], we present temperature dependent 2D spectra of laser dyes dissolved in glass-forming solvents. At low waiting times, the system has not yet relaxed, resulting in a spectrum that is elongated along the diagonal. At longer times, the system loses its memory of the initial excitation frequency, and the 2D spectrum rounds out. As the temperature is lowered, the time scale of this relaxation grows, and the elongation persists for longer waiting times. This can be measured in the ratio of the diagonal width to the anti-diagonal width; the behavior of this ratio is representative of the frequency–frequency correlation function [ Optics Letters 31 (2006), 3354–3356]. Near the glass transition temperature, the relaxation behavior changes. Understanding this change is important for interpreting temperature-dependent dynamics of biological systems.